PENGARUH KECERDASAN EMOSIONAL DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT DCM FATIH MEDIKA DI JAKARTA SELATAN - Nurhayati, Kiki; Kadarmanta, R.A. (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to determine the simultaneous effect of emotional intelligence and job satisfaction on the performance of employees at PT Dcm Fatih Medika, South Jakarta. The method used is a quantitative approach with an associative method. The research population consisted of 57 people, all of whom were sampled using a saturated sampling technique. Data analysis used instrument testing (validity and reliability), classical assumption testing (normality, multicollinearity, heteroscedasticity), multiple linear regression analysis, partial testing (t-test), simultaneous testing (F-test), and the coefficient of determination (R²). The results of the analysis show that emotional intelligence has a positive and significant effect on employee performance. This means that the higher the emotional intelligence of employees, the better their performance. Job satisfaction was found to have a positive and significant effect on employee performance, indicating that the higher the level of job satisfaction, the better the employee performance. Simultaneously, emotional intelligence and job satisfaction had a significant effect on the performance of employees at PT Dcm Fatih Medika Jakarta Selatan. The coefficient of determination (R²) of 0.494 shows that 49.4% of the variation in employee performance can be explained by emotional intelligence and job satisfaction. Meanwhile, the remaining 50.6% is influenced by other factors not examined in this study